MANAGEMENT OF COVID ASSOCIATED ORBITAL MUCORMYCOSIS IN TERTIARY CARE HOSPITAL - SRI SAI, VEJENDLA BHAVYA; PADMAVATHI, KATTOJU (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The aim of the study was to study epidemiological characteristics and management of orbital mucormycosis in cases of rhino-orbital mucormycosis in tertiary care hospital. Methods: It is a retrospective study of 258 patients presenting to KGH, Visakhapatnam, over a duration of 3 months from June to August 2021. After taking detailed history regarding symptoms of mucormycosis, visual acuity was noted, slit lamp examination was done and necessary investigations such as microbiology, pathology specimens were sent and analyzed, imaging done, and management done accordingly. Results: The majority of patients came with ENT-related symptoms were treated with endoscopic debridement, that is, 216 (84%), endoscopic debridement with orbital decompression of 23 (9%), transcutaneous retrobulbar amphotericin B of 21 (8%), orbital exenteration of 17 (6.5%), total and partial maxillectomy of 28 (10.8%), temporal lobe abscess drainage of 7 (2.7%), frontal lobe abscess drainage of (1.16%), frontal bone abscess drainage of 3 (1.16%), dural abscess drainage of 6 (2.3%), 15 (5.8) treated conservatively, and 30 (11.6%) death. Conclusion: COVID-19 infection in presence of glycemic dysregulation predisposes to development of Rhino-orbital-cerebral mucormycosis. Strict glycemic control and judicious use of corticosteroids might help in decrease incidence of mucormycosis cases. Most of the patients presents with ENT-related symptoms if not treated early may spread to orbit and intracranial sites. Early treatment during early presentation might help prevent spreading orbital extension and intracranial extension.